(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Ramadan fasting can affect mental and physical health due to changes in eating patterns and sleep patterns. This study aims to compare the Tabata training method with Circuit Training on sleep quality and mood disorders in students during Ramadan fasting. This study involved 30 male students who were randomly divided into Tabata training groups (n = 15) and Circuit training (n = 15). In Tabata training, participants did 8 rounds with 6 repetitions, while in Circuit training, participants did 6 rounds with 6 repetitions. After training, participants will fill out the Profile of Mood States (POMS) questionnaire which aims to measure mood after training and at dawn participants will fill out the Sleep Quality Scale (SQS) questionnaire for sleep quality. The results showed that Tabata training can improve sleep quality and reduce mood disorders, especially in terms of fatigue, tension, and depression compared to circuit training. These findings also show that higher intensity training such as Tabata has a good impact on sleep quality and mood during fasting. This study also explores the important role of exercise intensity and time in managing the challenges of fasting and provides insights into the use of tailored fitness programs during the fasting period.